Kartläggning av arbetsterapeutiska arbetssätt och insatser i olika faser av katastrofsituationer - En litteraturöversikt - Lilja,Josefin; Booth,Tiegan Jade (2025)
Background: The number of people affected by natural disasters, war, or conflicts is increasing. These disaster situations limit the ability of those affected to engage in important and meaningful activities. Occupational therapists have expertise in how person, environment, and activity interact and can contribute to efforts related to disaster situations and people affected by them. Aim: The aim was to identify the current state of knowledge regarding occupational therapists' approaches and interventions before, during, and after disaster situations. Method: A literature review with an inductive approach. Twelve scientific articles from the databases PubMed, CINAHL, and PsycINFO were included and analysed using integrative analysis. Results: The results showed that occupational therapists have a role in all phases of a disaster. The identified categories were risk reduction, flexible approach and varied tasks, working within socio-political rules, nature-based group interventions, weaving groups, and interventions focused on daily activities. Interventions were largely found in the aftermath of disasters and were aimed at providing social support, alleviating mental health issues, and offering culturally adapted meaningful activities to enhance quality of life Conclusion: There are few studies that highlight how occupational therapists work in connection with disaster situations. Yet the results indicate that therapists can carry out important interventions for disaster-affected people. Further research is needed to clarify and strengthen knowledge about the significance and potential of occupational therapy related to disaster situations and for affected individuals.
Keywords: Arbetsterapi; katastrof; krig; naturkatastrof; flykting; asylsökande Occupational therapy; disaster; war; natural disaster; refugee; asylum seeker; forced migration